1997
DOI: 10.1038/sj.bmt.1700626
|View full text |Cite
|
Sign up to set email alerts
|

Rapid immunologic reconstitution following transplantation with mobilized peripheral blood stem cells as compared to bone marrow

Abstract: Summary:ABMT may contribute to an improved clinical outcome. Further, patients receiving a PSCT may be more A majority of patients with intermediate or high-grade responsive to adjuvant immunotherapy following transnon-Hodgkin's lymphoma (NHL) who are treated with plantation. high-dose chemotherapy (HDT) and hematopoietic stem Keywords: PSCT; BMT; immunity; T cell; NHL; NK cell transplantation subsequently relapse. Until recently, cell F transplantation was associated with high morbidity and mortality and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
142
1
4

Year Published

1997
1997
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(153 citation statements)
references
References 12 publications
6
142
1
4
Order By: Relevance
“…[31][32][33][34] These studies also showed a more rapid regeneration of a normal CD4/CD8 ratio. In the autologous setting Talmadge et al 31 observed a normalised CD4/CD8 ratio and an improved cytotoxic and proliferative response even 3 months after PBPC treatment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[31][32][33][34] These studies also showed a more rapid regeneration of a normal CD4/CD8 ratio. In the autologous setting Talmadge et al 31 observed a normalised CD4/CD8 ratio and an improved cytotoxic and proliferative response even 3 months after PBPC treatment.…”
Section: Discussionmentioning
confidence: 97%
“…17,42 A high stem cell support may also be critical to a rapid reconstitution of T cells. 31,32 One recent study by Carabasi et al 43 investigating 10 adult patients after allogeneic CD34 + selected PBPC transplantation using Ͼ9 × 10 6 /kg CD34 + cells, median, showed a rapid normalisation of the CD4/CD8 ratio even by 2 months and a regrowth of CD3 + /CD45RA + cells, indicating a regeneration via newly produced T cells.…”
Section: Discussionmentioning
confidence: 99%
“…CD95 (Apo-1/Fas) is a member of the TNF/nerve growth factor superfamily that can directly transduce an apoptotic death signal on trimerization with Fas ligand (CD95L) or Fas-specific Abs (25,26). Fas is expressed on the surface of various cell types, including T cells, B cells, and macrophages, as well as cells of the liver, spleen, lung, testis, heart, brain, and intestine (27,28). Apoptosis provides one mechanism for the regulation of peripheral CD4 positive T-cell homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in the immune system over the first few months and years after ABMT and PBSCT have been extensively studied. 5,6 It is, however, still an open question whether complete normalization of CD4 ϩ T cells will occur in these patients.…”
mentioning
confidence: 99%